Air Exposure Affects Physiological Responses, Innate Immunity, Apoptosis and DNA Methylation of Kuruma Shrimp, Marsupenaeus japonicus - Wang, Panpan; Wang, Jun; Su, Yongquan; Liu, Zhixin; Mao, Yong (Frontiers in Physiology, 2020)
Air exposure stress is a common phenomenon for commercial crustacean species in aquaculture and during waterless transportation. However, the antioxidant responses to air exposure discussed in previous studies may be insufficient to present the complexities involved in this process. The comprehensive immune responses, especially considering the immune genes, cell apoptosis, and epigenetic changes, are still unknown. Accordingly, we investigated the multifaceted responses of Marsupenaeus japonicus to air exposure. The results showed that the expression profiles of the apoptosis genes (e.g., IAP, TXNIP, caspase, and caspase-3) and the hypoxia-related genes (e.g., hsp70, hif-1α, and HcY) were all dramatically induced in the hepatopancreas and gills of M. japonicus. Heart rates, T-AOC (Total antioxidant capacity) and lactate contents showed time-dependent changes upon air exposure. Air exposure significantly induced apoptosis in hepatopancreas and gills. Compared with the control group, the apoptosis index (AI) of the 12.5 h experimental group increased significantly (p < 0.05) in the hepatopancreas and gills. Most individuals in the experimental group (EG, 12.5 h) had lower methylation ratios than the control group (CG). Air exposure markedly reduced the full-methylation and total-methylation ratios (31.39% for the CG and 26.46% for the EG). This study provided a comprehensive understanding of the antioxidant responses of M. japonicus considering its physiology, innate immunity, apoptosis, and DNA methylation levels, and provided theoretical guidance for waterless transportation.